All girls - Layden, Emily, 1989- (St. Martin's Press, 2021)
"A keenly perceptive coming-of-age novel for fans of Sally Rooney, Curtis Sittenfeld, and J. Courtney Sullivan, All Girls captures one year at a prestigious New England prep school, as nine young women navigate their ambitions, friendships, and fears against the backdrop of a scandal the administration wants silenced. But as the months unfold, and the school's efforts to control the ensuing crisis fall short, these extraordinary girls are forced to discover their voices, and their power. A tender and unflinching portrait of modern adolescence told through the shifting perspectives of an unforgettable cast of female students, All Girls explores what it means to grow up in a place that promises you the world--when the world still isn't yours for the taking"--